TINDAKAN LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN MEMBERIKAN PERLINDUNGAN TERHADAP PEREMPUAN KORBAN KEKERASAN - Latiffah Fajar Rahayu; Dilla Hariyanti (Constitutum: Jurnal Ilmiah Hukum, 2022)
Violence against women in this era is no longer a taboo anti-mainstream issue to talk about. The phenomenon of violence against women has recently become a prominent issue in mass media coverage. Forms of violence, both physical, psychic, sexual, threatening, intimidation and emotional actions. All forms of violence experienced by these women, the more difficult it is for law enforcement to take legal action. The actions of the Witness and Victim Protection Agency to take measures to provide protection for women victims of violence still find obstacles where in the legal process. Often cases of violence against women victims are considered not to meet the elements of criminal acts, therefore, the legal process cannot be continued, even often the victim actually gets a reply from the perpetrator such as a counter-report, there needs to be a criminal law policy that provides legal protection for women as witnesses and victims of violence.